Instruments for the Scientific Dissemination of Archaeology in Alicante Between the Late 19th and Early 20th Centuries (1886-1910): The Journals El Archivo, El Ibero y Museo-Exposición - Olcina Lagos, Santiago (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2024)
The development of the archaeological discipline during the second half of the 19th century led, among many other things, to the creation of the first scientific journals, such as Revista de Archivos, Bibliotecas y Museos of the Faculty of Archivists, Librarians and Archaeologists, Museo Español de Antigüedades of the National Archaeological Museum and Boletín de la Real Academia de la Historia. Their example helped other institutions and individuals to publish journals with archaeological subjects with the aim of publicising their research work and other news related to heritage management. In this paper, we analyse from a historiographical point of view three journals founded in the province of Alicante between 1886 and 1910: El Archivo by Roque Chabás Llorens, El Ibero by Francisco Figueras Pacheco and Museo-Exposición by Miguel Elizaicin España.
Keywords: archaeological historiography; scientific dissemination; journals